Comparative study of total phenolic compounds, flavonoids and antioxidant capacities in pigmented and non-pigmented rice of indica rice varieties - Chutipaijit, Sutee; Sutjaritvorakul, Thanawat (My University, 2018)
The total phenolic compounds and flavonoid contents of grains as well as the antioxidant capacities were determined in 15 rice varieties. A high-performance liquid chromatography method was modified for the determination of the flavonoid subgroups in rice grains. The results showed the total phenolic compounds, flavonoid contents, and antioxidant capacities of pigmented rice were higher than in non-pigmented rice. The amounts of flavanone groups ranging from 0.04 to 0.40 mg Naringenin g−1, while flavones groups ranging from 0.08 to 0.57 mg Apigenin g−1, flavonol groups ranging from 0.16 to 1.20 mg Quercetin g−1 and anthocyanin groups ranging from 44.43 to 69.83 mg Cyanidin chloride g−1 were found in pigmented rice. The total phenolic compounds and total flavonoid contents of grains were significantly correlated with their antioxidant capacities. The results indicated that pigmented rice appeared as a good source of phenolic and flavonoid compounds and had beneficial nutritive values or antioxidant substances.
Keywords: Antioxidant activity; Flavonoids; HPLC; Phenolic compounds; Rice